P‐Wave Rejection in a Transplanted Heart - Lowery, Christopher M. (Ann Noninvasive Electrocardiol, 2011)
Background: Heart block can occur at multiple levels in patients with prior cardiac transplant. This diagnosis is usually ascertained using the surface electrocardiogram. Results: A 24‐year‐old man with prior cardiac transplant presented with apparent complete atrioventricular nodal block and junctional escape on the surface ECG. During pacemaker implantation, we demonstrated sinus rhythm in the recipient atrium, block across the atrioatrial anastomosis, and sinus arrest with intact AV nodal conduction in the donor atrium. Conclusion: This case illustrates an unusual presentation of sinus arrest occurring 2 years after heart transplantation that appeared to be complete heart block. Ann Noninvasive Electrocardiol 2011;16(3):308–310